The Effectiveness of Structured and Guided Inquiry Learning Models in Enhancing Students’ Science Process Skills on Acid-Base Topics in Senior High School - Kriswantoro; Melfiza; Haryanto; Muhammad Haris Effendi hasibuan (Jurnal Penelitian Pendidikan IPA, 2025)
Education is a key factor in shaping students' character and competence. The 2013 Curriculum highlights not only the development of student character but also the enhancement of scientific competence, including science process skills (SPS). One effective approach to developing SPS is through the application of inquiry-based learning models. This study investigates the differences in students' SPS on acid-base topics by comparing the use of structured inquiry and guided inquiry models. The research employed a random sampling technique, and data were collected using observation sheets and field notes. Field notes were analyzed qualitatively to support and enrich the interpretation of observational and quantitative findings. The quantitative data, obtained from essay-based tests, were analyzed using inferential statistics such as the Shapiro-Wilk normality test, homogeneity test, independent t-test, paired t-test, and N-Gain to evaluate learning improvement in both groups. The effectiveness of each model was determined based on the increase in N-Gain scores from pretest to posttest. The results revealed that inquiry-based learning significantly improved students' SPS, with an increase in the average score from 35.18 to 78.33. Additionally, observation data indicated a steady increase in students’ engagement and participation throughout the learning sessions, highlighting the benefits of inquiry approaches in science education.